Morphological Variations between Provenances of Vachellia abyssinica Hochst. ex Benth. and Cordia africana Lam. from Different Seed Sources in Ethiopia - Seid, Mohammed Adefa; Gebeyehu, Marshet Nigatu (Annals of Arid Zone, 2024)
Plants exhibit phenotypic plasticity, which means they can adapt their morphology in response to changes in the environment. The objective of this study was to assess the extent of morphological variations among different seed sources of Vachellia abyssinica and Cordia africana in Ethiopia. A total of 26 populations from natural vegetation for V. abyssinica and 58 populations for C. africana from farmlands were surveyed between 2019 and 2020. We computed hierarchical clustering (HC), one-way ANOVA with a significance level of p≤0.05, and redundancy analysis (RDA). The HC analysis resulted in five cluster groups for V. abyssinica, based on parameters such as height and DBH. The one-way ANOVA revealed significant differences in mean height and DBH among these cluster groups. The RDA showed that annual mean temperature (Bio01) and mean diurnal range (Bio02) have a highly significant impact on the morphological variability among the populations of V. abyssinica (p=0.001***). Similarly, we identified three cluster groups for C. africana based on height and DBH parameters. The one-way ANOVA demonstrated significant differences in mean height and DBH among these cluster groups. The RDA indicated that Bio02 had a very significant effect on the morphological variability among the populations of C. africana (p=0.01**), followed by Isothermality (Bio03) with a significant effect (p≤0.05*). The findings of this study can be applied to the management and domestication of V. abyssinica and C. africana.